ISLAMIC ARCHITECTURE FRAMEWORK: MENTIFACT, SOCIOFACT AND ARTEFACT - Nazaruddin, Farid; Firmansyah, Aldrin Yusuf; Samudro, Harida; Kurniawaty, Prima (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
This paper aims to rectify the prevailing perspective within architectural studies, which often focuses solely on the physical aspects of architecture, neglecting a profound analysis of its spiritual dimension. Islamic Architecture, as a significant cultural contribution of Islam to the world, transcends mere stylistic choices. It serves as an embodiment of Muslim values within the built environment, bridging spirituality with physicality. This paper delves into the fundamental principles of Islamic Architecture, drawing from classical Islamic sources and contemporary writings. The literature review categorizes the sources into three groups: mentalfact, sociofact, and artefact. The study reveals a profound philosophical foundation for Islamic Architecture, directly rooted in the teachings of the Al-Quran and Al-Hadith. Notably, Islamic Architecture places a strong emphasis on its social impact. Furthermore, these foundational principles evolve to create architectural beauty that holds distinct uniqueness and a sense of identity rooted in Islamic values.